Equilibrium Pricing and Optimal Hedging in Electricity Forward Markets - Bessembinder, Hendrik; Lemmon, Michael L. (Journal of Finance, 2002)
ABSTRACT Spot power prices are volatile and since electricity cannot be economically stored, familiar arbitrage‐based methods are not applicable for pricing power derivative contracts. This paper presents an equilibrium model implying that the forward power price is a downward biased predictor of the future spot price if expected power demand is low and demand risk is moderate. However, the equilibrium forward premium increases when either expected demand or demand variance is high, because of positive skewness in the spot power price distribution. Preliminary empirical evidence indicates that the premium in forward power prices is greatest during the summer months.